2008
DOI: 10.1098/rstb.2008.0154
|View full text |Cite
|
Sign up to set email alerts
|

Leaky Cl –HCO 3 exchangers: cation fluxes via modified AE1

Abstract: The abundant membrane protein AE1 normally functions as an obligate anion exchanger, with classical carrier properties, in human red blood cells. Recently, four single point mutations of hAE1 have been identified that have lost the anion exchange function, and act as non-selective monovalent cation channels, as shown in both red cell flux and oocyte expression studies. The red cell transport function shows a paradoxical temperature dependence, and is associated with spherocytic and stomatocytic red cell defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Other mutations in the membrane domain that cause erythrocyte abnormalities have milder effects on the rate of anion exchange ( Table 1 ), including E758K and R760Q ( Ellory et al, 2009 ; Stewart et al, 2010 ). E758 and R760 are located at the cytoplasmic end of TM11, in the transport domain ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Other mutations in the membrane domain that cause erythrocyte abnormalities have milder effects on the rate of anion exchange ( Table 1 ), including E758K and R760Q ( Ellory et al, 2009 ; Stewart et al, 2010 ). E758 and R760 are located at the cytoplasmic end of TM11, in the transport domain ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1 Furthermore, transfection of Xenopus leavis oocytes with cRNA from cloned mutant band 3 cDNA caused an increased content of Na + and a decreased content of K + ions upon incubation at ambient temperature under conditions that blocked the Na Collectively, these results suggested that the mutation may convert the band 3 protein from an anion exchanger to a non-selective cation channel. 9,10,12 It has been shown that activity of the NKCC is unaltered and that of the Na + /K + pump up-regulated due to the intracellular Na + accumulation in CHC erythrocytes. 1 The activities of the K + ,Cl -cotransporter (KCC) and of the cation-proton exchangers in the RBC of CHC patients have not been addressed.…”
Section: Resultsmentioning
confidence: 99%
“…The present data show that its substitution by Lys converts the exchanger into a cation leak whereas its substitution by Cys induces a cation leak in a still-functioning anion exchanger. Other point mutations in AE1 were shown to induce a cation leak in still-functional anion exchangers; however coexpression with AE1 chaperone glycophorin A was required to obtain significant expression to plasma membrane (17)(18)(19). This suggests that these point mutations have a more dramatic effect on AE1 conformation than that required to cause a cation leak.…”
Section: Involvement Of Ae1 Tm8 In Anion Exchange and Cation Leak-mentioning
confidence: 91%
“…However, in these variants human AE1 point mutations induce a cation conductance nonselective for Na ϩ and K ϩ (16). Depending on the mutations, we have proposed that the exchanger is either converted to a nonselective cation conductance or it can behave simultaneously as an anion exchanger and as a nonselective cation conductance (17)(18)(19). The specific point mutations involved in changes of the transport mechanism are associated with human pathologies such as distal renal tubular acidosis or hereditary hemolytic anemia (20 -23).…”
mentioning
confidence: 99%